IMPLEMENTASI PENGGUNAAN MODEL PJBL BERBANTUAN MEDIA WAYANG PANCASILA TERHADAP PENINGKATAN PEMAHAMAN IMPLEMENTASI SILA PANCASILA PESERTA DIDIK DI KELAS 2 SD NEGERI GISIKDRONO 02 - Arifa Ramadhani; Devi Fitriyani; Zahra Apriliana; Susilo Tri Widodo; Wulan Aulia Azizah; Vanda Asri Kaeksi Siswandari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The study aims to determine the improvement of the learning outcomes of the students using the Project Based Learning (PjBL) model supported by the learning media “Wayang Pancasila” on the implementation of Pancasila in everyday life. The type of research used in this research is qualitative research with a descriptive qualitative approach. Data collection using interviews, observations, written tests, and documentation. The validation technique used is triangulation technique. Subjects in this study are teachers and students of class II A SD State Gisikdrono 02 Semarang. The results obtained in this study are the presence of increased understanding of students related to the implementation of the precepts of Pancasila after given the treatment of learning using the PjBL model and media Wayang Pancasila.`